New Religious Movement di Indonesia: Studi Kasus Agama Pran-Soeh di Yogyakarta - Shadiqin, Sehat Ihsan (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2011)
This paper describes the dynamics and development of Pran-Soeh: the local Javanese mysticism with followers of approximately 700 people in Yogyakarta and Central Java. It concludes that the emergence of Pran-Soeh is motivated by its followersâ move to acommodate the mainstream religius belief with the local Javanese mysticism at the backdrop of mounting pressures from the spread of other formal religious belief in the country. As a minority religious group, Pran-Soehâs historical development has been very much influenced by its dialectical interaction with other formal religion in Indonesia. The article also highlights that the hegemony of the government-endorsed religiosity has obstructed the development of Pran-Soeh.